2014
DOI: 10.2217/nmt.14.24
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Review of Instrumental Activities of Daily Living in Dementia: what’s cooking?

Abstract: The measurement of instrumental activities of daily living (IADL) is common in clinical practice and research into dementia. IADL are cognitively complex daily activities, such as cooking and doing finances. Their measurement is required for the diagnostic process of dementia, and also useful for the monitoring of disease progression. Since problems in IADL contribute to the disease burden of both patient and caregiver, it is a relevant outcome measure for disease-modifying and non-pharmacological intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 60 publications
2
47
0
3
Order By: Relevance
“…With our chosen cutoff, we defined more patients as slow progressors in IADL as compared to CDR-SB or MMSE scores. This is probably due to the psychometric qualities of the questionnaire, which may not have the necessary responsiveness to change [33].…”
Section: Discussionmentioning
confidence: 99%
“…With our chosen cutoff, we defined more patients as slow progressors in IADL as compared to CDR-SB or MMSE scores. This is probably due to the psychometric qualities of the questionnaire, which may not have the necessary responsiveness to change [33].…”
Section: Discussionmentioning
confidence: 99%
“…De fait, sont dites complexes, les activités qui relèvent de multiples processus cognitifs incluant des processus de haut niveau, les processus contrôlés, c'est-à-dire la gestion d'opérations de prise de décision, d'organisation- [18], compte tenu de la proximité des deux définitions, nous avons opté pour une définition commune : « Les IADL sont des activités intentionnelles et complexes pour lesquelles de multiples fonctions cognitives sont nécessaires, particulièrement les processus contrôlés de haut niveau ».…”
Section: Dad-6 : Version Abrégée De La Dad (Disability Assessment Forunclassified
“…Chacune des méthodes d'évaluation a son intérêt et ses limites [18]. L'interrogation de patients souffrant de démence n'est pas toujours fiable et les mises en situation sont difficilement réalisables et sont de plus discutables en raison de leur caractère artificiel.…”
Section: Résultatsunclassified
“…Default network dysfunction has been also associated with IADL impairment [7], and a post-mortem study demonstrated a relationship between global amyloid pathology and ADL impairment in severe Alzheimer’s disease [8]. Thus, a description of IADL and ADL is useful in assessing the way cognitive impairments interfere with daily functioning, a reliable indicator of cognitive disorders or dementia [9, 10]. The Lawton and Brody scale for IADL [11] and the Katz scale for ADL [12] are commonly used to assess dependency among elderly people in Western countries.…”
Section: Introductionmentioning
confidence: 99%